Investigation of the Effect on Photosensitivity following Multiple Oral Dosing of Two Different Hypericum Extracts in Healthy Men - Schulz, Hans-Ulrich; Schürer, Michael; Bässler, Dagmar; Weiser, Dieter (Arzneimittelforschung, 2006)
The naphthodiantrones hypericin and pseudohypericin, ingredients of hypericum extracts, are known as potent photosensitizers that may cause phototoxic effects in grazing animals after excessive ingestion of hypericum species and in some cases in higher concentrations of hypericum extracts oder pure hypericin in humans as well.Therefore, the objective of the present studies was to investigate the effect of two different hypericum extracts (STW 3, STW 3-VI) on photosensitivity with respect to minimal erythema dose (MED) after 14 days treatment. Both open, multiple-dose, one-phase studies were conducted in 20 healthy men, receiving one tablet per day. MED values were determined prior to hypericum extract administration (baseline) and after 14 days treatment using an erythem tester emitting a light very similar to sun light (main emission spectrum: 285—350 nm). Skin reactions with respect to MED were evaluated 12 h, 24 h (primary endpoint), 48 h and 7 days after irradiation.All volunteers reached steady-state of hypericin/pseudohypericin plasma concentrations before study day 14, when the irradiation under treatment conditions took place. In all subjects MED was measurable under baseline and under hypericum treatment conditions. With respect to the primary endpoint, in both studies, mean MED (24 h) were not significantly different between baseline and after 14 days hypericum treatment. However, individually photosensitivity of the skin could increase under treatment conditions, just as well photosensitivity could decrease or remain unchanged. There were no clinically relevant changes in the laboratory parameters, the vital signs, physical findings and other observations related to safety during the examinations. In one study (STW 3), two adverse events were reported, both described as hypersensitivity to light in mild intensity.The two studies showed that treatment with the two hypericum extracts under steady state and under prescribed conditions were safe medications without significant increases of photosensitivity.
Keywords: Antidepressants; Hypericin, minimal erythema dose, photosensitivity, skin reaction; Hypericum perforatum